Bis-Quinolinium Cyclophane Blockers of SK Potassium Channels Are Antagonists of M3 Muscarinic Acetylcholine Receptors - Bugay, Vladislav; Wallace, Derek J.; Wang, Bin; Salinas, Irving; Chapparo, Adriana Paola; Smith, Hudson Ryan; Dube, Peter Herbert; Brooks, Edward G.; Berg, Kelly Ann; Brenner, Robert (Frontiers in Pharmacology, 2020)
Dequalinium is used as an antimicrobial compound for oral health and other microbial infections. Derivatives of dequalinium, the bis-quinolinium cyclophanes UCL 1684 and UCL 1848, are high affinity SK potassium channel antagonists. Here we investigated these compounds as M3 muscarinic receptor (mACHR) antagonists. We used the R-CEPIAer endoplasmic reticulum calcium reporter to functionally assay for Gq-coupled receptor signaling, and investigated the bis-quinolinium cyclophanes as antagonists of M3 mACHR activation in transfected CHO cells. Given mACHR roles in airway smooth muscle (ASM) contractility, we also tested the ability of UCL 1684 to relax ASM. We find that these compounds antagonized M3 mACHRs with an IC50 of 0.27 μM for dequalinium chloride, 1.5 μM for UCL 1684 and 1.0 μM for UCL 1848. UCL 1684 also antagonized M1 (IC50 0.12 μM) and M5 (IC50 0.52 μM) mACHR responses. UCL 1684 was determined to be a competitive antagonist at M3 receptors as it increased the EC50 for carbachol without a reduction in the maximum response. The Ki for UCL1684 determined from competition binding experiments was 909 nM. UCL 1684 reduced carbachol-evoked ASM contractions (>90%, IC50 0.43 μM), and calcium mobilization in rodent and human lung ASM cells. We conclude that dequalinium and bis-quinolinium cyclophanes antagonized M3 mACHR activation at sub- to low micromolar concentrations, with UCL 1684 acting as an ASM relaxant. Caution should be taken when using these compounds to block SK potassium channels, as inhibition of mACHRs may be a side-effect if excessive concentrations are used.